Effect of toe wedges on the biomechanics of the forward lunge in badminton - Gammelgaard, M. S.; Ahlers, F. H.; Lam, W.-K.; Rasmussen, J.; Kersting, U. G. (ISBS Proceedings Archive (Michigan), 2017)
The badminton lunge movement accounts for 15% of all actions in a competitive single match. The purpose of this study was to assess the effects of different toe wedges during a forward badminton lunge. Eighteen healthy male subjects participated in the study where the biomechanics and performance of three different wedge conditions were evaluated (0 mm, 4 mm and 8 mm toe elevation). Ground reaction forces and kinematic data were in a laboratory. Results showed an increased peak ankle moment for the 8-mm wedge compared to 0-mm (P=0.003) and 4-mm (P=0.028) wedges along with a reduced hip flexion moment (P=0.049 and P=0.034, respectively), while the time to task completion remained unchanged. Results indicate that joint moments may be altered by badminton footwear with implications for fatigue.